PENGARUH PROFESIONALISME APARAT TERHADAP PELAYANAN PUBLIK DI DESA TIMORENG PANUA KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Abdul Rahmat Ali; Muhammad Ikbal; Saifullah Saifullah (PRAJA: Jurnal Ilmiah Pemerintahan, 2021)
The purpose of this research is to determine the effect of professionalism of the apparatus on the Public Service of Timoreng Panua, Panca Rijang District, Sidenreng Rappang Regency. The population in conducting this research is the whole community who have received services and community leaders with male and female sex with 696 family heads. The sampling technique used is the Yount Table with the results of 70 samples, taken based on purposive sampling technique. The type of research used is quantitative descriptive research. Data collection techniques used are using observation techniques, questionnaires, and literature study. Data analysis technique is using validity, reliability using SPSS 16.0 and Likert Scale. Based on research taken from the results of the questionnaire, it was obtained that the recapitulation of Bureaucratic Behavior variable was 62.9% including the "Good" category. Recapitulation of Service Quality variable of 65.1% included in the category of "Good".